Upaya Negara Dalam Mencapai Keamanan Energi. Studi Kasus: Transformasi Kebijakan Energi Korea Selatan - Ardila Putri (Frequency of International Relations (FETRIAN), 2022)
The export-based development policy launched by South Korea after the end of the Korean war caused the country to rely heavily on energy sources for their development goals. This ultimately encourages South Korea to continue transforming its energy policy in accordance with the situation and conditions experienced by the country. This paper analyzes South Korea's energy transition since its establishment to the present day using the multi-level perspective. The transition process was analyzed from the relationship between the existing regime and innovation opportunities in the wider environment. Data was collected through official South Korean government documents, websites, also supported by journals and news articles. This study concludes that the government remains the dominant actor at the meso level in any energy policy transition. As for the micro level, there are differences in innovation opportunities according to the conditions in that era. In addition, energy transitions are also caused by different situation in each period at the macro level.